Revitalizing the Japanese economy by socializing risk - Charles Yuji Horioka; Reiko Kanda (Osaka University, Institute of Social and Economic Research (ISER), 2010)
The almost continuous stagnation of the Japanese economy for the past two decades has had an adverse impact on Japanese households from at least three perspectives: A decline in the standard of living, an increase in risks and uncertainties relating to livelihood, employment, old age, etc., and an increase in income inequality. The majority of economists and policymakers focus their attention on the increase in income inequality. The research discussed here, however, focuses on the increase in risk and uncertainty among households and individuals. Based on this research, we propose a shift to a policy regime centering on the socialization of risk, which will make possible a transition from a society in which individuals bear excessive risks to one in which risk is shared equitably by society as a whole.
Keywords: G20; H11; H50; I38; J08; J70; P10; P51; 330; Japanese economy; Policy regimes; Liberal regime; Social democratic regime; Conservative regime; Economic risks; Risk-coping mechanisms; Risk sharing; Socialization of risk; Social welfare; Redistribution; Government expenditures; Income gap; Income disparities; Income inequalities; Discrimination; Child care; Nursing care; Employment; Work-life balance; Bankruptcy; Financial products; Poverty; Collectivist entities; Policy recommendations; Wirtschaftswachstum; Verteilungswirkung; Politisches Ziel; Soziale Ungleichheit; Soziale Lage; Privater Haushalt; Sozialstaat; Wirtschaftliche Anpassung; Japan